A pilot study assessing the brain gauge as an indicator of cognitive recovery in alcohol dependence. (8th March 2021) - Powell, Anna; Tommerdahl, Mark; Abbasi, Yasir; Sumnall, Harry; Montgomery, Catharine
Abstract: Alcohol dependence (AD) is associated with multiple cognitive deficits, which can affect treatment outcomes. Current measures of tracking brain recovery (e.g., functional magnetic resonance imaging) can be less accessible for practitioners. This study pilots a novel device (the brain gauge; BG) to assess its utility, and track recovery of cognitive function in residential alcohol treatment. Methods: A repeated measures design assessed changes in cognitive function during detoxification. Twenty‐one participants with AD (16 Male; Mean age 43.85 ± 6.21) completed a battery of alcohol and memory questionnaires and BG tasks at two time‐points (∼days 4 and 10) during a single managed detoxification episode. Results: Repeated measures ANCOVA revealed that some BG metrics significantly improved, with medium to large effect sizes ‐ processing speed, focus, temporal order judgement and overall cortical metric. However, differences in subjective cognitive function were non‐significant after controlling for depression and anxiety change scores. Anxiety change emerged as a significant factor in subjective cognitive function. Conclusions: We conclude it is possible that the prefrontal cortex (PFC) recovers more slowly compared to other brain areas, and there are compounding effects of improvements in anxiety and depression, and metacognitive deficits on subjective EF assessments. Future research should seek to validate the clinical utility of the BG by comparing against established neuroimaging methods.